Cell adhesion-dependent inactivation of a soluble protein kinase during fertilization in Chlamydomonas. - Zhang, Y (1996)
Within seconds after the flagella of mt+ and mt- Chlamydomonas gametes adhere during fertilization, their flagellar adenylyl cyclase is activated several fold and preparation for cell fusion is initiated. Our previous studies indicated that early events in this pathway, including control of adenylyl cyclase, are regulated by phosphorylation and dephosphorylation. Here, we describe a soluble, flagellar protein kinase activity that is regulated by flagellar adhesion. A 48-kDa, soluble flagellar protein was consistently phosphorylated in an in vitro assay in flagella isolated from nonadhering mt+ and mt- gametes, but not in flagella isolated from mt+ and mt- gametes that had been adhering for 1 min. Although the 48-kDa protein was present in the flagella isolated from adhering gametes, we demonstrate that its protein kinase was inactivated by flagellar adhesion. Immunoblot analysis and inhibitor studies indicate that the 48-kDa protein in nonadhering gametes is phosphorylated by a protein tyrosine kinase. In vivo experiments showing that the protein tyrosine phosphatase inhibitor sodium orthovanadate inhibits fertilization suggest that protein dephosphorylation may be required for signal transduction. The 48-kDa protein and its protein kinase may be among the first elements of a novel signalling pathway that couples interaction of flagellar adhesion molecules to gamete activation.